2017
DOI: 10.1111/clr.13010
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge dimensional changes following ridge preservation procedure with novel devices: part 3 – histological analysis in non‐human primate model

Abstract: SocketKAP™ + SocketKAGE™ devices proved effective in reducing post-extraction alveolar bone resorption mediating favorable wound healing within sockets. Addition of ABBM was associated with reduced volumetric loss, although the bone fill was characterized by less mature as well as more woven bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…[1][2][3] Previous animal studies reporting dimensional change have been performed in fresh extraction sockets. [4][5][6][7][8] However, if teeth with a severe inflammatory state are extracted, bone resorption may be more extensive and altered, 2 and alveolar bone destruction may influence the optimal placement of dental implants. 2 Thus, ridge preservation techniques have been performed to prevent alveolar dimensional change.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Previous animal studies reporting dimensional change have been performed in fresh extraction sockets. [4][5][6][7][8] However, if teeth with a severe inflammatory state are extracted, bone resorption may be more extensive and altered, 2 and alveolar bone destruction may influence the optimal placement of dental implants. 2 Thus, ridge preservation techniques have been performed to prevent alveolar dimensional change.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that significant bone resorption occurs as an inevitable biological event following tooth extraction without additional intervention [ 1 11 ]. The rates of loss of alveolar bone width and height in the first three months following extraction are approximately 0.25 mm and 0.2 mm, respectively [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various biomaterials used for ridge preservation have been evaluated including autograft [ 18 , 19 ], allograft [ 20 ], xenograft [ 18 , 21 25 ], and alloplast [ 24 , 26 – 28 ]. These graft materials have been protected by different barrier devices, including resorbable membranes [ 20 , 29 , 30 ], nonresorbable membranes [ 31 ], autogenous soft tissue plugs [ 32 ], and extraction socket devices [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even if teeth with a severe inflammatory state are extracted, bone resorption may be more aggressive, and alveolar bone destruction may influence the perfect placement of the dental implant. (2)(3)(4) Xenogenous bone grafts (e.g., Bio-Oss ®) have long been used in the treatment of periodontal bone defects. Bovine-Derived Xenograft (BDX) (Bio-Oss®) has osteoconductive properties and high biocompatibility that undergoes chemical extraction process by which all organic components are removed maintaining the natural architecture of bone.…”
Section: Introductionmentioning
confidence: 99%